Live endoscopy events (LEEs): European Society of Gastrointestinal Endoscopy Position Statement – Update 2021 - Webster, George J.; El Menabawey, Tareq; Arvanitakis, Marianna; Hassan, Cesare; van Hooft, Jeanin E.; Messmann, Helmut; Dinis-Ribeiro, Mário (Endoscopy, 2021)
The European Society of Gastrointestinal Endoscopy (ESGE) is dedicated to improving the quality of gastrointestinal endoscopy, including through educational activities such as live endoscopy events (LEEs). The primary goal of LEEs should be to facilitate the improvement of endoscopic patient care through the acquisition of best endoscopic practice. Patients should not expect additional benefit from being treated during a LEE compared to a routine setting. There is limited available evidence on LEE safety but to date there is no indication that patients are at increased risk from participation. Pre-recorded cases with live facilitation can also be used to fulfill learning outcomes. Establishing an endoscopic curriculum with clear learning outcomes is important to structure attendees’ learning, assess course outcomes, and allow appropriate targeting of courses to learner experience. Increasingly, LEEs are streamed online and therefore the necessary measures should be taken to ensure that patients have given appropriate consent and that their anonymity has been safeguarded. ESGE recommends that an endoscopist who is not participating in the live demonstrations is named as patient advocate, and that patient safety should must be prioritized throughout. In all ESGE-organized LEEs the intended learning outcomes, procedural indications and descriptions, attendee feedback, and adverse events should be recorded and submitted in a post-event report to ESGE.